PENGARUH KEPUASAN KERJA, KOMITMEN DAN PROMOSI JABATAN TERHADAP TURNOVER INTENTION PADA KARYAWAN PT. ORINDO ALAM AYU CABANG PEKANBARU - Evitamala Sari; Nuryanti Nuryanti; Iwan Nauli Daulay (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research held in PT. Orindo Alam Ayu Pekanbaru. This research held in order to analyze the influence of job satisfaction, commitment and job promotion to employees’ turnover intention. Population are all employees, consist of 42 people. Considering the number limitation so sampling method used is census that covers all employee as the respondents. Variables used are job satisfaction commitment and job promotion as independent and employees’ turnover intention as dependent. Data analyzed by using descriptive analysis and multiple regression analysis by using SPSS 17 for windows. Result of this study shows that either simultenously or partially job satisfaction commitment and job promotion negative and significantly influence employees’ turnover. However, partially, only training gives significant effect to employees’ performance. Commitment is proved as the most dominant factor that influence employees’ turnover intention. It is recommended to company for enhancing employees’ job satisfaction, strengthening employees’ commitment and providing wider opportunity of job promotion by justice and transparant-base program.Keywords: Job Satisfaction, Commitment, Job Promotion and Turnover Intention